Decorin induces rapid secretion of thrombospondin‐1 in basal breast carcinoma cells via inhibition of Ras homolog gene family, member A/Rho‐associated coiled‐coil containing protein kinase 1. (15th February 2013) - Neill, Thomas; Jones, Holly R.; Crane‐Smith, Zoe; Owens, Rick T.; Schaefer, Liliana; Iozzo, Renato V.
<x xml:space="preserve">Abstract</x> Pathological neovascularization relies on an imbalance between potent proangiogenic agents and equally effective antiangiogenic cues. Collectively, these factors contribute to an angiogenic niche within the tumor microenvironment. Oncogenic events and hypoxia contribute to augmented levels of angiokines, and thereby activate the so‐called angiogenic switch to promote aggressive tumorigenic and metastatic growth. Soluble decorin functions as a paracrine pan‐inhibitor of receptor tyrosine kinases, such as Met and epidermal growth factor receptor, and thus is capable of suppressing angiogenesis under normoxia. This leads to noncanonical repression of hypoxia‐inducible factor 1‐alpha and vascular endothelial growth factor A (VEGFA), and concurrent induction of thrombospondin‐1. The substantial induction of endogenous tumor cell‐derived thrombospondin‐1, a potent antiangiogenic effector, led us to the discovery of an unexpected secretory phenotype occurring very rapidly (within 5 min) after decorin treatment of the triple‐negative basal breast carcinoma cell line MDA‐MB‐231. Surprisingly, the effect was not mediated by Met receptor antagonism, as initially hypothesized, but required epidermal growth factor receptor signaling to achieve swift and robust thrombospondin‐1 release. Furthermore, this effect was ultimately dependent on the prompt degradation of Ras homolog gene family member A, via the 26S proteasome, leading to direct inactivation of Rho‐associated coiled‐coil containing protein kinase 1. The latter led to derepression of thrombospondin‐1 secretion. Collectively, these data provide a novel mechanistic role for Rho‐associated coiled‐coil containing protein kinase 1, in addition to providing the first conclusive evidence of decorin exclusively targeting a receptor tyrosine kinase to achieve a specific effect. The overall effects of soluble decorin on the tumor microenvironment would cause an immediately‐early as well as a sustained antiangiogenic response in vivo.